The Physical and Sound Absorption Property of Lightweight Rigid Polyurethane Composite Reinforced Bamboo Fiber for Roof Applications - Roseli, Adyla Illyana; Mat Hassan, Nik Normunira; Abdul Mutalib Leman, Abdul Mutalib Leman; Abdul Latif, Najibah; Yulfian Aminanda, Yulfian Aminanda; Djoko Setyanto, Djoko Setyanto; Yuyun Tajunnusa, Yuyun Tajunnusa; Yonrapach Areerob, Yonrapach Areerob; Methawee Nukunudompanich, Methawee Nukunudompanich (semarak ilmu, 2023)
Rigid polyurethane (RPU) foams as roof insulation have become increasingly popular in Southeast Asian countries and have been extensively used for absorbing sound and reducing noise because of their good sound damping, viscoelasticity, and low density. In this study, the RPU foam composite reinforced bamboo fiber was investigated by physical characterization by SEM, TGA, and FTIR, and the sound absorption was measured by the Impedance Tube Test. The morphology result of the RPU foam composite indicates the size of the diameter pore influenced the sound absorption by adding bamboo fiber as a filler. The thermal degradation of the presence of lignin in the bamboo fiber at the temperature range of 400 °C to 500 °C and the total weight loss is 76 % at 429 °C temperature. FTIR spectrum shows that the peak at 2890 to 2935 cm-1 are indicated –CH stretching vibrations and characteristics for bamboo fiber can be used in polymer composites. The sound absorption of RPU 25 foam composite reinforced bamboo fiber was found 0.74 absorbance at a frequency of 1250 Hz. RPU foam reinforced bamboo fiber as a filler has the highest transmission loss RPU 35 is 21 dB at a frequency range of 1600 Hz. The findings indicate by increasing the content of bamboo fiber as filler, the diameter of the open pore of RPU 25 and RPU 35 foam composite had the potential for sound absorption to absorb at low frequency to achieve greater sound absorption for roof insulation.